Living unrelated kidney donor transplantation in Iran - Nobakht Haghighi, Ali; Ghahramani, Nasrollah (مجله اخلاق پزشکی - علمی پژوهشی, 2016)
In the September and November 2006 issues of Nature Clinical Practice Nephrology, two articles regarding living unrelated kidney donor transplantation alluded to the practices in Iran. Having served in the planning, supervision and implementation of various aspects of health care in Iran, including organ transplantation (ANH), and as transplant nephrologists who have actively participated in the care of transplanted patients in Iran (ANH and NG), we feel obligated to elucidate the realities surrounding organ transplantation in Iran. So that unbiased researchers are provided with information to judge for themselves.